Impacts and Implications of Macro Determinants Toward the Indonesian Sharia Stock Index - Rahman, Akhlis Auliya; Widodo, Syukri Fathudin Achmad; Andni, Riyan; Muflih, Betania Kartika (IQTISHADIA, 2023)
This study aims to analyze the effect of inflation, interest rates, exchange rates, and the Indonesian Composite Stock Price Index (IHSG) on the Indonesian Sharia Stock Index (ISSI), which is based on the inconsistencies of previous studies regarding inflation results, interest rate results, exchange rate results, as well as the results of the ISHG against the ISSI. This study uses a quantitative approach. The research data source uses secondary data in the first quarter of 2012 – fourth quarter of 2022 in the form of the closing price of the ISSI from https://www.ojk.go.id/ then the closing price for inflation, interest rates, exchange rates from https://www. ojk.go.id/ www.bi.go.id/, and the closing price of the Indonesian composite index from https://finance.yahoo.com/, which were processed using SPSS 26 software with multiple linear analysis. The results showed that inflation, interest rates, and exchange rates partially had no significant effect on the ISSI. Meanwhile, the IHSG had a significant effect on the ISSI. The variables of inflation, interest rates, exchange rates, and the IHSG simultaneously affect the ISSI. These results have implications for policymakers regarding the Islamic capital market.